2017
DOI: 10.1021/acsomega.7b01189
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Isomaltooligosaccharides by Saccharomyces cerevisiae Cells Expressing Aspergillus niger α-Glucosidase

Abstract: The α-glucosidase encoded by the aglA gene of Aspergillus niger is a secreted enzyme belonging to family 31 of glycoside hydrolases. This enzyme has a retaining mechanism of action and displays transglycosylating activity that makes it amenable to be used for the synthesis of isomaltooligosaccharides (IMOs). We have expressed the aglA gene in Saccharomyces cerevisiae under control of a galactose-inducible promoter. Recombinant yeast cells expressing the aglA gene produced extracellular α-glucosidase activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 40 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…α-Glucosidases of filamentous fungi have been suggested as feasible catalysts for transglycosylation. Thus, an Aspergillus enzyme with high transglycosylating activity was reported to produce panose and isomaltose from maltose [18,59,60]. When an A. nidulans α-glucosidase with strong transglycosylating activity was reacted with 5 g/L maltose during 6 h, approximately 50% of maltose was converted to transglycosylation products, 60% of which was isomaltose [60].…”
Section: Discussionmentioning
confidence: 99%
“…α-Glucosidases of filamentous fungi have been suggested as feasible catalysts for transglycosylation. Thus, an Aspergillus enzyme with high transglycosylating activity was reported to produce panose and isomaltose from maltose [18,59,60]. When an A. nidulans α-glucosidase with strong transglycosylating activity was reacted with 5 g/L maltose during 6 h, approximately 50% of maltose was converted to transglycosylation products, 60% of which was isomaltose [60].…”
Section: Discussionmentioning
confidence: 99%
“…(2017) and Casa‐Villegas et al . (2017) when homology models of α‐glucosidase from A. niger strains were used. Docking studies also showed Phe693, Thr694, Thr228, Trp343, Met491 and Trp453 as the adjacent sites to catalytic site (cf.…”
Section: Discussionmentioning
confidence: 99%
“…S3). SphI-treated pYES2-PαXC-rDNA, linearized at the rDNA loci, was transformed into S. cerevisiae INVSc1 using the optimized LiAC/ssDNA chemical method [19] .…”
Section: Construction Of Multi-copy Xynb S Cerevisiae Invsc1-pyes2-pmentioning
confidence: 99%
“…Because HAC1 contains a 250-bp intron, it is not expressed in normal S. cerevisiae cells. However, when improperly folded proteins accumulate in the ER, HAC1 is spliced, the intron is removed, and active HAC1 protein is expressed [19] . Therefore, in the current study, improper protein folding was induced in wild-type S. cerevisiae using DTT, a protein folding inhibitor, allowing amplification of activated HAC1.…”
Section: Effects Of Overexpression Of Hac1 On the Expression Of Xylanmentioning
confidence: 99%
See 1 more Smart Citation